Association between plasma betaine levels and dysglycemia in patients with coronary artery disease. Issue 8 (17th August 2020) - Guo, Fei; Qiu, Xueting; Zhu, Yuanting; Tan, Zhirong; Li, Zhenyu; Ouyang, Dongsheng
Abstract: Background: Dietary betaine intake was reported to associate with favorable profile of metabolic disorders. However, the role of circulating betaine in coronary artery disease (CAD) patients with dysglycemia is still unknown. The present study aimed to investigate the potential associations between plasma betaine levels and dysglycemia in CAD patients. Methods: Total 307 subjects were enrolled in the present study with 165 CAD patients (57 with dysglycemia and 108 with normal glycemia) and 142 age- and sex-matched controls (CON). Fasting plasma betaine was detected using liquid chromatography tandem mass spectrometry. Results: Plasma betaine was lower in normal glycemia CAD patients (28.29 (22.38–35.73) μM) compared with healthy controls (29.75 (25.32–39.15) μM), and was further decreased in CAD patients with dysglycemia (24.14 (20.84–30.76) μM, P <0.01). Betaine levels were inversely correlated with fasting glucose, glycated hemoglobin% (HbA1c), diastolic blood pressure (DBP), triglyceride (TG) and alanine aminotransferase (ALT) levels (all, P ≤0.05). Subjects in the highest betaine tertile group had lowest frequency of CAD and dysglycemia (all, P <0.01). Increased betaine levels were independently associated with low risk of dysglycemia in CAD after adjustment for multiple traditional risk factors (OR = 0.04, 95% CI: 0–0.37, P =0.01). Furthermore, betaine had good performance at distinguishing CAD with dysglycemia from normal glycemia CAD (AUC = 0.62, P <0.01). Conclusion: Plasma betaine levels are independently and inversely associated with dysglycemia in CAD after adjustment for multiple factors, and may be useful for risk stratification of dysglycemia in CAD.